Introduction - Valenti, Giorgio; Ceda, Gian Paolo (Acta Biomedica Atenei Parmensis, 2010)
This fifth Meeting on Geriatric Endocrinology held in Parma on March 27-28 2009 was an up-todate revision of the most recent findings on the tight bi-directional interconnections between aging and endocrine system...